The Influence Of Adding Superplasticizer With Time Interval And Variation Of Water Reduction On The Early Strength And Workability Of Concrete - Mochammad Tommy Frediyansyah; Sukamta Sukamta; Rizki Aulia Sulistyowati; M.Muhtajul Umam; Han Ay Lie (Green Publisher Indonesia, 2024)
Acceleration of early strength of concrete can be obtained by reducing water in the concrete mixture followed by addition of superplasticizer. The application of the addition of superplasticiser to water-reduced concrete mixtures requires innovation in providing a time lag to produce good workability. This study analyzes the effect of giving a time delay when adding superplasticizer followed by reducing water with certain variations on the workability and early strength of concrete. The results of this research are very important for the concrete industry with the purpose of shortening the removal time of formwork and optimizing the construction process. Water cement ratio is adjusted by reducing its volume by a fraction of 10% to 30%, superplasticizer 1% to the weight of cement is added in two stages, during the initial mixing and after one or two hours afterwards. 0.3% retarder was added to control homogeneity during mixing. The test results concluded that the reduction of water that provided the highest increase in concrete compressive strength at 4 days was LN25-1 of 21.94 MPa (87% of the design compressive strength) and LN20-2 of 19.12 MPa (76% of the compressive strength plan). The optimal amount of water reduction at the initial age of the concrete is 20 – 25% of the design water weight. Giving a time lag does not reduce the increase in concrete strength due to the addition of superplasticizer.